Analysis of Students ' Ability to Understand Mathematical Concepts In Terms of Learning Interests - Mario Dos Santos Amaral; Urni Babys; Netty Julinda Marlin Gella (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Understanding the concept is the ability to absorb and understand mathematical ideas and interest in learning are the impulses in students psychically in learning something with full awareness, calmness, and discipline to cause individuals actively and happy to do it. This study aims to analyze the ability of students to understand mathematical concepts in terms of learning interests. The subjects in this study were MIA2 grade students of Christian High School 2 Soe even semester school year 2021/2022 as many as 30 students. The method used in this study is descriptive qualitative data collection techniques using tests, questionnaires, and interviews. The data analysis technique follows the Miles and Huberman model with a validity test of data using the triangulation technique. The results showed that the ability of students to understand mathematical concepts in terms of learning interests varies. Students with a high level of interest in learning by 20% were able to achieve four out of six indicators of the ability to understand mathematical concepts. Students with a moderate level of interest in learning 63% were able to achieve three indicators of understanding mathematical concepts. Students with a low level of interest in learning 17% were able to achieve two indicators of understanding mathematical concepts.